Maqṣid Sūraħ Yūsuf ‘Alaihi Al-Salām Dirāsaħ Tahlīliyyaħ Muqāranaħ: مقصد سورة يوسف عليه السلام، دراسة تحليلية مقارنة - Sameh Salem Abdelhamid (ZAD Al-Mufassirin, 2021)
This research aims to find out the purpose of Surat Yusuf (as) The approach to this research is analytical and comparative to the library study (library research). The most important findings of this research first: Youssef's story is the surah. Surah is his story and its purpose: God is dominant in his command and to confirm the surah that God is dominant in his command, he notes that the word science and its derivatives are frequently received secondly: the reason for the descent of some verses of the Surah is more closely related to its purpose. Thirdly, the words of the Qur'anic stories are made according to the purpose of the Surah. Fourth: starting and closing in the surah may not only depend on a word or a verse, but also There may be a set of verses that make up this.